The Effect of Emotional and Stress Management Class on Stress Levels of Thai Students at Thammasat University - จิตวโรภาส, รุ่งรัตน์; รสเครือ, พิชญานุช; เทเลอร์, อารี; นวลละออง, วินิทรา (Journal of the Psychiatric Association of Thailand, 2019)
Objectives : To investigated stress levels of freshman and sophomore students (Science and Technology, Health Sciences, Social Science and Humanities) before and after attending one class on emotional and stress management. Methods : This research was a pretest-posttest study without control group using the self-reported stress test (Suan Prung Stress Test; SPST-20). The data analysis was performed with both descriptive and inferential statistics. Results : Three thousand four hundred and fifty-nine students [male 990 (28.6%)] completed the questionnaires. The mean (±standard deviation) pre and post class stress levels were 47.22±13.52 (high stress) and 35.89±12.49 (moderate stress), respectively (p<0.01), and were similar between the three groups of students. Conclusions : Once class on emotional and stress management successfully reduced stress in this broad range of Thai university students and represented a good strategy for maintaining student health. More research is needed to evaluate its long term effect and its role in as part of a broad strategy of stress reduction in students.